DDD pacing in hypertrophic cardiomyopathy: a multicentre clinical experience. Issue 1 (January 1996) - Slade, A. K.; Sadoul, N.; Shapiro, L.; Chojnowska, L.; Simon, J. P.; Saumarez, R. C.; Dodinot, B.; Camm, A. J.; McKenna, W. J.; Aliot, E.
Abstract : BACKGROUND--DDD pacing has been advocated as an effective treatment for drug refractory obstructive hypertrophic cardiomyopathy. This study reports the outcome of pacing in 56 patients with refractory symptoms referred to four tertiary centres. METHODS--Core data on symptoms, drug burden, and left ventricular outflow tract gradient were recorded. Patients underwent a temporary pacing study with optimisation of the atrioventricular (AV) delay for greatest gradient reduction without haemodynamic compromise. Patients were assessed after implantation in terms of changes in symptoms, drug load, and outflow tract gradient. RESULTS--56 patients underwent pacing assessment. The mean (SD) left ventricular outflow tract gradient before pacing was 78 (31) mm Hg. At temporary study the mean (SD) left ventricular outflow tract gradient was 38 (24) mm Hg with a median (range) optimised sensed AV delay of 65 (25-125) ms. Fifty three patients were implanted and followed up for a mean (SD) of 11 (11) months. The median (range) programmed sensed AV delay was 60 (31-200) ms. Left ventricular outflow tract gradient at follow up was 36 (25) mm Hg. Forty four patients had improved functional class. Although a correlation (r = 0.69) was shown between acute and chronic left ventricular outflow tract gradient reduction, there was no correlation between magnitude of gradient reduction and functional improvement, and no appreciable change in pharmacological burden. CONCLUSION--This series confirms symptomatic improvement after DDD pacing in hypertrophic cardiomyopathy. There remains, however, a discrepancy between perceived symptomatic benefit and modest objective improvement. Furthermore, the optimal outcome has been achieved only with continued pharmacological treatment. Current methods of temporary evaluation do not predict functional outcome which seems to be independent of the magnitude of gradient reduction.